Identification and distribution of a single nucleotide polymorphism responsible for the catechin content in tea plants. (1st March 2020) - Jiang, Chen-Kai; Ma, Jian-Qiang; Liu, Yu-Fei; Chen, Jie-Dan; Ni, De-Jiang; Chen, Liang
Abstract: Catechins are the predominant products in tea plants and have essential functions for both plants and humans. Several genes encoding the enzymes regulating catechin biosynthesis have been identified, and the identification of single nucleotide polymorphisms (SNPs) resulting in nonsynonymous mutations within these genes can be used to establish a functional link to catechin content. Therefore, the transcriptomes of two parents and four filial offspring were sequenced using next-generation sequencing technology and aligned to the reference genome to enable SNP mining. Subsequently, 176 tea plant accessions were genotyped based on candidate SNPs using kompetitive allele-specific polymerase chain reaction (KASP). The catechin contents of these samples were characterized by high-performance liquid chromatography (HPLC), and analysis of variance (ANOVA) was subsequently performed to determine the relationship between genotypes and catechin content. As a result of these efforts, a SNP within the chalcone synthase ( CHS ) gene was shown to be functionally associated with catechin content. Furthermore, the geographical and interspecific distribution of this SNP was investigated. Collectively, these results will contribute to the early evaluation of tea plants and serve as a rapid tool for accelerating targeted efforts in tea breeding.